Data from 990 Public Real-World Job Advertisements Organized by O*NET Categories - Steven Zhou; John Aitken; Peter J. McEachern; Renee McCauley (Journal of Open Psychology Data, 2022)
Text from 990 job advertisements were downloaded from companies on the Fortune 500 2020 list of top companies. These job ads covered 32 different job titles from eight industries. The responsibilities and requirements sections were saved for each job, and, when available, city, state, salary, company size, and other offered text were saved. Data were collected manually by a team of researchers during the summer of 2021 through a systematic search process. The dataset is stored on the OSF. Data can be used for further job advertising analysis and comparison.